Prenatal Diagnosis of Orofacial Malformations - Tonni, Gabriele; Sepulveda, Waldo; Wong, Amy E. (Springer International Publishing : Imprint: Springer, 2017)
This book describes how different diagnostic techniques may facilitate the prenatal identification of orofacial malformations. The role of standard two-dimensional ultrasound is documented and explained, but detailed attention is also paid to the use of three-dimensional (3D) ultrasound, including the novel 3D reslicing technique, and to the value of complementary magnetic resonance imaging. The malformations considered include cleft lip, cleft lip and palate, ocular malformations, abnormalities associated with fetal aneuploidy, and tumors. These conditions are depicted in numerous high-quality images accompanied by thorough and informative descriptions of imaging findings. The excellence of the illustrative material and the caliber of the authors, who are leading international experts in the field, ensure that Prenatal Diagnosis of Orofacial Malformations will be an invaluable tool for obstetricians and gynecologists.